2002
DOI: 10.1016/s1044-0305(02)00354-9
|View full text |Cite
|
Sign up to set email alerts
|

Ion trap mass spectrometry affords advances in the analytical and atmospheric chemistry of 2-hydroxy-2-methylpropanal, a proposed photooxidation product of 2-methyl-3-buten-2-ol

Abstract: In the western United States, in areas where emissions of the biogenic hydrocarbon, 2-methyl-3-buten-2-ol (MBO) are high, MBO contributes significantly to the oxidative capacity of the atmosphere. Hydroxyl radical oxidation of MBO can play an important role in forming tropospheric ozone, and MBO reaction products may contribute to the formation of secondary organic aerosols [1][2][3]. Although 2-hdyroxy-2-methylpropanal was tentatively identified as a product from the reaction of MBO with ⅐OH in indoor chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…All the tested compounds presented a neutral loss of 181 amu (C 6 F 5 N) among other ions. This type of fragmentation was previously observed in other studies when analyzing pentafluorobenzylhydroxylamine PFBHA38, 39 and PFPH derivatives of carbonyl compounds 32, 33. Neutral loss scans were performed in order to confirm the previous results and 19 of the 24 compounds under study were detected under neutral loss scanning of 181 amu.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…All the tested compounds presented a neutral loss of 181 amu (C 6 F 5 N) among other ions. This type of fragmentation was previously observed in other studies when analyzing pentafluorobenzylhydroxylamine PFBHA38, 39 and PFPH derivatives of carbonyl compounds 32, 33. Neutral loss scans were performed in order to confirm the previous results and 19 of the 24 compounds under study were detected under neutral loss scanning of 181 amu.…”
Section: Resultssupporting
confidence: 78%
“…Moreover, the results obtained with oxoacids suggested that the signal intensity was enhanced when the distance between the ketone and the carboxyl group increased. Nevertheless, additional experiments involving a higher number of oxoacids would be required to confirm this observation, and the α‐oxoacids were rarely reported in the literature contrarily to ω‐oxoacids that have been often identified in atmospheric POM samples 38–43…”
Section: Resultsmentioning
confidence: 83%
“…Therefore, the PFBHA and PFBHA‐BSTFA derivatives of 2‐HMPR were identified by interpreting the EI, methane CI, and PFBOH CI ion trap mass spectra, and by matching the relative retention times and mass spectra to those of a peak obtained from the reaction of MBO with hydroxyl radical in an atmospheric chamber experiment. Identification was later confirmed by matching the relative retention time and mass spectra to that from a derivative of a synthesized authentic standard [ Spaulding et al , 2002b].…”
Section: Methodsmentioning
confidence: 99%
“…However, in previous work we compared this method to FT‐IR measurements in which 2‐HMPR mixing ratios were estimated by assuming a yield 29% (equal to the yield of formaldehyde) from the reaction of MBO with OH radicals. According to this comparison, the error of the method ranges from 6 to 41%, depending on the assumed yield of 2‐hydroxy‐2‐methylpropanal [ Spaulding et al , 2002b].…”
Section: Methodsmentioning
confidence: 99%
“…The reaction proceeds almost totally by initial addition of HO to the C=C bond (Fantechi et al, 1998b;Ferronato et al, 1998;Alvarado et al, 1999;Spaulding et al, 2002;Reisen et al, 2003;Carrasco et al, 2007). In the presence of NO at atmospheric pressure of air the observed products are formaldehyde, acetone, glycolaldehyde, 2-hydroxy-2-methylpropanal [(CH3)2C(OH)CHO], and dihydroxynitrates [presumed to be (CH3)2C(OH)CH(OH)CH2ONO2 and (CH3)2C(OH)CH(ONO2)CH2OH] (Fantechi et al, 1998b;Ferronato et al, 1998;Alvarado et al, 1999;Spaulding et al, 2002;Reisen et al, 2003;Carraso et al, 2007).…”
Section: Comments On Preferred Valuesmentioning
confidence: 99%